Finite Element Analysis of Maxillary Teeth Movement with Time during En Masse Retraction Using Orthodontic Mini-Screw - Jeong-Bo Hwang; Sung-Seo Mo (Applied Sciences, 2023)
Introduction: The aim of this study was to determine the placement of an orthodontic mini-screw (OMS) and the length of an anterior retraction hook (ARH) with en masse retraction. Continuous maxillary tooth movement pattern was simulated by finite element analysis (FEA). Materials and methods: Extraction of the first premolar was hypothesized with a finite element model. The placement of OMS was analyzed for the following two groups: (1) a high OMS (HOMS) group with OMS placed horizontally at the mesial side of the second premolar and apically 10 mm above the arch wire, and (2) a low OMS (LOMS) group with OMS placed horizontally between the second premolar and the first molar and apically 8 mm above the arch wire. According to the height of ARH, each group was divided into three subgroups. Results: When the extraction space of the first premolar was closed, anterior teeth were intruded in the HOMS group but extruded in the LOMS group. In all cases, the first molar was intruded. According to the intrusion of the first molar and extrusion of anterior teeth, the occlusal plane rotated clockwise (CW) in the LOMS group. However, in the HOMS1 group, the occlusal plane rotated counterclockwise (CCW) due to more intrusion of anterior teeth than that of the first molar. Conclusion: By analyzing six cases of different OMS and ARH, changes of incisor and molar in en masse retraction with the extraction of the first premolar could be predicted. In addition, OMS placement and ARH length can be determined based on results of incisal showing. This study can also help esthetic orthodontic results.